Possibilities of University Teaching Enhancement - Integration of Methods and Approaches in Teaching Literature with Science and Social Studies - Olivera D. Cekić-Jovanović; Snežana P. Marković (University of Belgrade, Teacher Education Faculty, 2021)
Starting from the established standards and requirements for ensuring the quality of university teaching, via improving and modernizing the teaching process by applying innovative teaching methods, conditions are met for raising the quality of working with students. Integration of the teaching content and application of an integrative approach represent a way of enhancing the quality of the teaching process. The theoretical part of this paper presents the advantages and examples of the integration of the Literature Teaching Methodology and Science and Social Studies Teaching Methodology curriculum content. In order to practically implement the theoretical context for the development of this idea, we examined the views of students at the Faculty of Education, i.e. future teachers (N=150), regarding the integration of teaching approaches to teaching Literature and Science and Social Studies as opportunities for enhancing the quality of university education. Descriptive and scaling methods were used in the empirical part of the research. The results of the research have confirmed that students recognize the benefits of integrative teaching and its importance for their future professional engagement; they expect to cooperate with teachers and students in the preparation and realization of integrative classes; and they define the integration of methodological content as the premise of quality for the acquired knowledge at the faculty, and see it as one of the preconditions for a better understanding of the subject matter they adopt in the teaching process. The latter statement underscores the conclusion that the application of integrative teaching represents a good starting point for ensuring the quality of higher education following the European standards.